2020
DOI: 10.1021/acs.jafc.0c00641
|View full text |Cite
|
Sign up to set email alerts
|

Manganese in the Diet: Bioaccessibility, Adequate Intake, and Neurotoxicological Effects

Abstract: Manganese (Mn) is an essential element that participates in several biological processes. Mn serves as a cofactor for several enzymes, such as glutamine synthetase and oxidoreductases, that have an important role in the defense of the organisms against oxidative stress. The diet is the main source of Mn intake for humans, and adequate daily intake levels for this metal change with age. Moreover, in higher amounts, Mn may be toxic, mainly to the brain. Here, we provide an overview of Mn occurrence in food, addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 130 publications
(223 reference statements)
0
25
0
Order By: Relevance
“…Alteration of these processes, under Mn deficiency or excess conditions, may result in severe metabolic dysfunction. However, the case for dietary Mn deficiency appears to be extremely rare in humans due to high levels of Mn in dietary products [7,8]. In contrast, Mn overexposure, which is far more common, may cause brain-associated disorders [9].…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of these processes, under Mn deficiency or excess conditions, may result in severe metabolic dysfunction. However, the case for dietary Mn deficiency appears to be extremely rare in humans due to high levels of Mn in dietary products [7,8]. In contrast, Mn overexposure, which is far more common, may cause brain-associated disorders [9].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Chronic overexposure to Mn is known to cause neurotoxicity, referred to as manganism, a parkinsonism-like disorder. [9] Severe outcomes of Zn dyshomeostasis are largely due to malnutrition, which is especially prevalent in the elderly population. Vural et al, for example, reported that an insufficient daily Zn intake (defined as below the estimated average requirement (EAR) of 6.8 mg Zn⋅day -1 for women and 9.4 mg Zn⋅day -1 for men) was observed in 31-66% of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Chronic overexposure to Mn is known to cause neurotoxicity, referred to as manganism, a parkinsonism‐like disorder. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, people who consume 28 mg/L of water containing high levels of elements such as Mn can develop toxicity [ 73 ]. Although Mn is an essential nutrient, especially regarding the reduction of oxidative stress, both Mn deficiency or overload is rare, whereas the excess is usually caused by environmental exposure [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%